Relationality, culpability and consent in wartime: men's experiences of forced marriages - Aijazi, Omer (International journal of transitional justice)
Rights-based approaches to forced marriage in wartime document forms of harm women experience, to the exclusion of men’s experiences. Such framing problematically reiterates a binary of women/men, victim/perpetrator and consent/coercion. Arguably, this delineation is useful in supporting projects of culpability and legal redress. However, what does such vocabulary obfuscate or render invisible? We draw from the experiences of men demobilized from the Lord’s Resistance Army (LRA) and presently living in northern Uganda to consider how relationships and social accountabilities are governed in settings of coercion. We argue that forced marriage in wartime cannot be understood without examining the multiple relationalities on which it is contingent. We broaden the remit of men’s relationships to women in the LRA to consider how men’s relations to each other and to their children shaped their experiences of marriage during the war. We conclude by reflecting on concepts of consent and culpability in coercive settings.